Ion dynamics of non-stoichiometric Na0.5+xBi0.5-xTiO3-δ: A degradation study - Singh P.; Jha P.K.; Sinha A.S.K.; Jha P.A.; Singh P. (My University, 2025)
Sodium bismuth titanate, a well-known piezoelectric material is reported as the new family of fast oxide ion conductors. In the current study, we investigated the influence of A-site non-stoichiometry on the electrical conductivity and ion dynamics of sodium bismuth titanate ceramics. For this, we synthesized the system Na0.5+xBi0.5-xTiO3–δ with x = −0.02, −0.01, 0.00, 0.01 and 0.02. The samples synthesized were almost single phase with rhombohedral (R3c) symmetry. The scanning electron micrographs showed the formation of dense grains with bulk density > 96%. The microstructure appeared to be very sensitive to non-stoichiometry. The conductivity data isotherms with frequency showed non-linear variation and were well fitted with Jonscher power law. We have observed super linear frequency dependent behaviour in Bi rich composition and sub-linear behaviour with the increase in Na content. To study the degradation mechanism, Na0.5+xBi0.5-xTiO3-δ (x = −0.01, 0.00, 0.01) samples were kept in reducing environment for 48 h. Further, for the analysis of conduction mechanism and the qualitative/quantitative estimation of charge carriers before and after reducing conditions, various models were used. © 2019 Elsevier B.V.